Design, synthesis and biological evaluation of novel 1, 3, 4, 9-tetrahydropyrano[3, 4-b]indoles as potential treatment of triple negative breast cancer by suppressing PI3K/AKT/mTOR pathway. (1st February 2022) - Qin, Jing; Sun, Xia; Ma, Yingang; Cheng, Yahong; Ma, Qiushuang; Jing, Weiqiang; Qu, Sifeng; Liu, Lei
Graphical abstract: Highlights: Molecular hybridization is a useful tool for construction of small molecule library. Compound 23 possess anti-cancer effects and selectivity against MDA-MB-231 cells. Compound 23 showed inhibitory effect against PI3K/AKT/mTOR pathway. Compound 23 is novel TNBC drug candidate by inducing cell cycle arrest and apoptosis. Abstract: Triple-negative breast cancer (TNBC) represents a subset of breast cancer characterized by high aggressiveness and poor prognosis. Currently, there is no curative therapeutic regimen for TNBC patients. In this study, molecular hybridization strategy is adopted by combining benzopyran and indole pharmacophores together, and a library of structurally simple 1, 3, 4, 9-tetrahydropyrano[3, 4- b ]indoles was rapidly constructed. The structure-activity relationship studies indicated that compound 23 exhibited the most potent effect against the MDA-MB-231 cells with IC50 value of 2.29 μM. Mechanistic studies revealed that compound 23 inhibited cell proliferation via arresting cell cycle at G0/G1 phase. It induced cell apoptosis by disruption of mitochondrial membrane potential (MMP), accumulation of reactive oxygen species (ROS), reduction of glutathione (GSH), elevation of intracellular calcium ion (Ca 2+ ) and activation of caspase cascade. Furthermore, compound 23 significantly inhibited the regulators of PI3K/AKT/mTOR pathway in MDA-MB-231 cells, suggesting that PI3K/AKT/mTOR pathway was involved in the 23- mediated apoptosis. To our knowledge, this is the first example of the anti-cancer activity study of indole-fused pyrans through suppressing PI3K/AKT/mTOR pathway. Overall, the current study suggested that compound 23 would serve as a promising lead compound for TNBC treatment.